PENGARUH PRICE DISCOUNT DAN DISPLAY TOKO TERHADAP IMPULSE BUYING PADA PELANGGAN SUZUYA ROCKY PLAZA PADANG - Candrianto Candrianto; Mutiara Novennica; Erwinsyah Sipahutar (JURNAL ILMIAH TEKNOLOGI INDSUTRI (SAINTI), 2019)
The purpose of this study was to analyze the effect of price discountand store display on impulse buying in customers at Suzuya Rocky Plaza Padang. This type of research is causative research. The population of this study was all Suzuya in customers at Suzuya Rozky Paza Padang who had experienced failure in the process of unplanned shopping (Impulsive buying). While the number of research samples is determined based on the accidental sampling method. So that the resulting sample is 100 people. The data used are primary data obtained through distributing questionnaires to selected customers. This study has two categories of variables. First is the independent variable, namely price discount and store display. The two dependent variables are impulse buying. The analytical method used is descriptive and quantitative analysis through multiple regression analysis. The results showed that the price discount and store display had a significant effect on impulse buying in customers at Suzuya Rocky Plaza Padang.